The Effect of Glazing Cover Material on Box-Type Solar Cooker performance: Pengaruh Bahan Penutup Kaca terhadap Kinerja Kompor Surya Tipe Kotak - Muhammad Naufal Bari; Damora Rhakasywi; Fahrudin (Universitas Muhammadiyah Sidoarjo, 2026)
This study compares two types of glass materials applied to a box-type solar cooker, namely low-iron glass and soda-lime glass. Low-iron glass is produced with a reduced iron oxide content, resulting in a higher transparency level compared to soda-lime glass, which affects its optical properties, particularly transmittance. The testing was conducted under two conditions: a stagnation test and a load test using 1 kg of water. The results indicated that the soda-lime glass system was superior, successfully boiling water up to 101.25 °C with a thermal efficiency of 0.48, an F1 value of 0.22, and an F2 value of 0.51. In contrast, the low-iron glass failed to boil the water, as the temperature only reached 79.25 °C, and it did not meet the load test feasibility standard, recording an F2 of 0.13 and an efficiency of 0.25.